2019
DOI: 10.12982/cmujns.2019.0012
|View full text |Cite
|
Sign up to set email alerts
|

Properties Changes of Chicken Breast during Sous-Vide Cooking and Acceptance for Elderly

Abstract: The sous-vide process has been used in cooking to maintain nutrients and improve texture of meat. This improvement in nutrients and softening of the texture could be advantageous for the elderly. The objective of this research was to study effects of sous-vide cooking on the properties and changes of chicken breast fillet and their sensory acceptance by the elderly. Chicken breast fillets were vacuum packed and cooked at 60 o C for different times from 1 to 8 h comparing the effects with a common way of cookin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…It was processed by having the vacuum-seal of the raw meat and then cooked in a water bath under precisely controlled temperature and time ( Baldwin, 2012 ). Numerous previous studies have demonstrated that SV-cooked chicken meat offers more favorable/better organoleptic characteristics, improved nutritional values, and decreased risk of post-cooking contamination during storage ( Kerdpiboon et al, 2019 ; Park et al, 2020 ; Haghighi et al, 2021 ; Hasani et al, 2022 ; Muthulakshmi et al, 2022 ). As a result, it has gained widespread adoption in catering services and food processing, providing foods of superior sensory quality.…”
Section: Introductionmentioning
confidence: 99%
“…It was processed by having the vacuum-seal of the raw meat and then cooked in a water bath under precisely controlled temperature and time ( Baldwin, 2012 ). Numerous previous studies have demonstrated that SV-cooked chicken meat offers more favorable/better organoleptic characteristics, improved nutritional values, and decreased risk of post-cooking contamination during storage ( Kerdpiboon et al, 2019 ; Park et al, 2020 ; Haghighi et al, 2021 ; Hasani et al, 2022 ; Muthulakshmi et al, 2022 ). As a result, it has gained widespread adoption in catering services and food processing, providing foods of superior sensory quality.…”
Section: Introductionmentioning
confidence: 99%